Creating sustainable entrepreneurship: Cross-sectional qualitative in-depth interviews to describe Durban SME entrepreneurs’ perception of motivation for entrepreneurship using key success factors - Kriel, Shannah (The IIE, 2017)
Studies from the Global Entrepreneurship Monitor (GEM) had shown, South Africa (SA) had a lack of entrepreneurship as it continued to drop below 38 percent from 2015, but SA was in desperate need for it to better South African lives through job creation and contributing to economic development (Herrington & Kew, 2016). South Africans were also said to lack motivation to achieve; as many people in SA needed only to survive, therefore understanding the key success factors for and finding ways to encourage entrepreneurship could have encouraged potential entrepreneurs to strive for success (Khan, 2014). A qualitative, in-depth interview questionnaire was used to gather information from four successful entrepreneurs that had more than ten years’ experience in entrepreneurship; because it was necessary to have gained a deeper understanding of the key success factors available to create a successful business and to find ways to encourage entrepreneurship. However, from this study, McClelland’s Achievement Motivation theory was rejected in a South African context and the combination of the participant’s responses could be used to form the key success factors that could guide potential SA entrepreneurs to success.
Keywords: Entrepreneurship; Global Entrepreneurship Monitor (GEM); Job Creation